Tingkat Tutur Pengisi Fungsi Subjek Bahasa Korea dan Bahasa Jawa - Iva Hanani; Suray Agung Nugroho (JLA (Jurnal Lingua Applicata), 2020)
The aim of this study is to explain Korean and Javanese subject honorific and identify its similarities and differences. To accomplish it, this research was conducted using literature review method. Data related to the Javanese language were taken from two Javanese drama scripts, namely Mak Ana Asu Mlebu Ngomah and Bantul Sangsaya Pinunjul, and Javanese drama titled Sri Ngilang by George Quinn. Korean language data was taken from television drama, Misaeng and Fight for My Way. Based on the analysis that has been carried out, despite the difference of the honorific system of Korean dan Javanese, Javanese has subject honorific as described in the Korean honorific system. Both languages use words that have honorific meaning to honor the subject and use words that are usually used for the animal to dishonor the subject of the sentence. The difference between both languages on subject honorific is Korean subject honorific is mainly realized grammatically, whereas in Javanese is realized lexically. In addition, there are rules from the Korean government regarding the use of one type of subject honorific, abjonbeob, whereas in Javanese there are no rules related to the use of speech level.